The concept of sport initiation nowadays - Sixto González Víllora; Luis Miguel García López; Onofre Ricardo Contreras Jordan; David Sánchez-Mora Moreno (FEADEF, 2009)
TIn this paper a wide analysis of bibliography related to the definition of sport initiation in the last decades is presented for this reason we have carried out a new view of the concept of games teaching in the early years from three points of view. First, teaching methods that have focused now on product, rather than on results. Second, teaching games concept has evolved from vertical to thematic approaches. Third, the context where sport is carried out, outlining leisure-health, education and competition-high performance. Finally we state that coexist as a result of linking this three points of view. One is more traditional, focusing games teaching on product, one sport and, in a certain way, on performance. On the other hand, second perspective is more focused on process, on thematic approaches and educational or leisure goals.